KONTRIBUSI GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBINAAN SIKAP MODERASI BERAGAMA PADA SMA NEGERI 13 BONE - Amir, Nurzakiyah (Adaara: Jurnal Manajemen Pendidikan Islam, 2022)
This study discusses the contribution of Islamic religious education teachers in fostering an attitude of religious moderation at SMA Negeri 13 Bone. As for the purpose of this study, namely, to determine the contribution of Islamic Religious Education teachers in fostering religious moderation in SMA Negeri 13 Bone. This research is a qualitative research (Qualitative Research). The approaches in this study are normative approaches, pedagogic approaches, sociological approaches and psychological approaches. Data collection techniques used are observation, interviews and documentation. The data obtained is then processed through data reduction, data presentation, and drawing conclusions. The results of the study show that the contribution of Islamic Religious Education teachers in fostering religious moderation at SMA Negeri 13 Bone, Islamic Religious Education teachers have given the best to students through inculcating tolerance values with learning activities with methods such as providing exemplary, giving directions, habituation, activities Rohis:, and the use of media in learning. All students are guided and fostered according to their talents and interests without distinguishing between religious backgrounds, especially for academic achievement and all school stakeholders have never shown the slightest sign of discrimination at SMA Negeri 13 Bone